Potret Ludruk Rukun Budaya sebagai Pusat Industri Kreatif Seni Pertunjukan di Kabupaten Probolinggo - Ramadani, Nur; Wahyuningtyas, Tri; Gusanti, Yurina (Mahesa Research Center, 2023)
This article investigates the dynamics of the Ludruk Rukun Budaya creative performing arts industry led by Harun. Since its formation on December 12, 2012, Ludruk Rukun Budaya has successfully established itself as a self-sustaining venture with a patronage model. The origin of Ludruk Rukun Budaya stems from Harun's experiences as a Ludruk performer in Madura and Situbondo, providing the foundation for establishing Ludruk in Probolinggo. The community's attraction to Ludruk Rukun Budaya lies in Harun's uniqueness, encompassing elements such as distinctive performances, daily life-reflecting dances, unique humor, and historically themed stories. This article details the captivating factors that attract audiences and explains why Ludruk Rukun Budaya has taken root in the hearts of the Probolinggo community. The research method employs a qualitative descriptive approach with Ludruk performers as the main informants, including Havin Suharon (42 years old), Untung Suropati (39 years old), Sareat (43 years old), and Dios (32 years old). Data analysis is conducted descriptively and interpretatively. Findings indicate that the success of Ludruk Rukun Budaya as a creative industry can be attributed to the cultural reproduction agent model of Harun, involving his experiences as an actor, ability to manage members, and a deep understanding of Ludruk audience preferences in Probolinggo.